Decreased likelihood of schooling as a consequence of tropical cyclones: Evidence from 13 low- and middle-income countries - Renzhi Jing; Sam Heft-Neal; Zetianyu Wang; Jie Chen; Minghao Qiu; Isaac M. Opper; Zachary Wagner; Eran Bendavid (Proceedings of the National Academy of Sciences, 2025)
Increasing educational attainment is one of the most important and effective strategies for health and economic improvements. The extent to which extreme climate events disrupt education, resulting in reduced educational attainment, remains understudied. Children in low- and middle-income countries (LMICs) may be uniquely vulnerable to losing schooling after disasters due to the poor physical condition of schools and the lack of resources to mitigate unexpected household shocks. Our analysis assesses this overlooked social cost of tropical cyclones on schooling attainment. We study the education records of nearly 5.4 million individuals living in 13 LMICs that experienced tropical cyclones between 1954 and 2010. By comparing individuals living in the same locations but with different exposure levels, we estimate the change in the likelihood that a preschool-age child exposed to tropical cyclone received no schooling. We find that exposure during preschool age is associated with a 0.5 percentage point increase in the likelihood of never attending schooling (2.5% above baseline), with larger effects (up to 8.8% increase) from stronger storms. These effects are more pronounced among girls and are greater in areas less adapted to tropical cyclones. Between 2000 and 2020, we estimate that 79,000 children in the 13 study countries did not start school due to tropical cyclones, and, across all affected students, tropical cyclones resulted in a total loss of 1.1 My of school. These impacts, identified among some of the world’s poorest populations, may grow in importance as exposure to severe tropical cyclones is projected to increase with climate change.